Order, Disorder and Counter-Order: the Relation between Action and Contemplation in the Thought of Gregory the Great Starting from the Tres Ordines Fidelium Scheme (Doctor Virtualis, 2024)
In the writings of Gregory the Great, the tres ordines fidelium scheme (praedicatores-continentes-coniugati) delineates the three forms of life that constitute the Church. This article investigates the reasons behind their hierarchical order: praedicatores at the pinnacle, continentes in the middle, and coniugati at the bottom of the scheme. Starting from an analysis of these three figures, the article underscores their relationship with the concepts of active life and contemplative life. Specifically, the configurations of the hierarchy between action and contemplation emerge as crucial to understanding the ecclesiological order of the tres ordines fidelium. These configurations are elucidated through the concepts of order and counter-order. In fact, while Gregory generally acknowledges the superiority of the contemplative life over the active life (🡪 order), he regards a mixed life that integrates action and contemplation as the highest form of life (🡪 counter-order). These observations seem to justify why, although the contemplative life of continentes is deemed superior to the active life of coniugati, the mixed life of praedicatores ascends the top of the hierarchy. In the concluding section, the article emphasizes the transversal role of active and contemplative life in the structure of the tres ordines fidelium. Representing two aspects that characterize the forms of life of each ordo, they reveal how the scheme of the tres ordines fidelium simultaneously expresses the anthropological components of the Church and three paradigms of spiritual progress.
Keywords: Gregory the Great; Order; Action; Contemplation; Ecclesiology